2016
DOI: 10.1080/0284186x.2016.1219047
|View full text |Cite
|
Sign up to set email alerts
|

Physical performance measures for predicting outcome in cancer patients: a systematic review

Abstract: Background: Decision making regarding cancer treatment is challenging and there is a need for clinical parameters that can guide these decisions. As physical performance appears to be a reflection of health status, the aim of this systematic review is to assess whether physical performance tests (PPTs) are predictive of the clinical outcome and treatment tolerance in cancer patients. Methods: A literature search was conducted on 2 April 2015 in the electronic databases Medline and Embase to identify studies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 42 publications
4
106
0
1
Order By: Relevance
“…Moreover, and to the best of our knowledge no studies have compared performance-based to self-report measures among patients with cancer to identify the best predictive measures for functional decline 34 although one study has compared the utility of different self-report and physical performance measures to predict mortality, the most extreme manifestation of functional decline. Among 200 women 65 years of age and older with gynecological cancers, Cesari M, et al, 35 compared six measures which included the VES-13, usual gait speed, SPPB, grip strength, ECOG Performance Status Scale, Karnofsky Performance Status Scale, ADL and IADL on their abilities to predict one-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and to the best of our knowledge no studies have compared performance-based to self-report measures among patients with cancer to identify the best predictive measures for functional decline 34 although one study has compared the utility of different self-report and physical performance measures to predict mortality, the most extreme manifestation of functional decline. Among 200 women 65 years of age and older with gynecological cancers, Cesari M, et al, 35 compared six measures which included the VES-13, usual gait speed, SPPB, grip strength, ECOG Performance Status Scale, Karnofsky Performance Status Scale, ADL and IADL on their abilities to predict one-year mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the first chemotherapy infusion (study baseline), research staff assessed the physical function of the participants using 2 measures: the Timed Up and Go test 25,26 and the Short Physical Performance Battery. 27,28 Additional patient-reported measures At baseline, study participants completed questionnaires for patient-reported measures of function and quality Cancer September 1, 2019 of life: the patient-reported Karnofsky performance status, 29 Medical Outcomes Survey (MOS) of physical function, 30 Functional Assessment of Cancer Therapy-General (FACT-G; version 4), 31 Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F; version 4), 32 and Mental Health Index-13 (MHI-13).…”
Section: Research Staff-assessed Physical Functionmentioning
confidence: 99%
“…Prior work showed that in younger patients with cancer, high symptom burden can negatively affect physical function, quality of life, and survival . Impaired physical function was shown to predict worse outcomes such as higher mortality and lower quality of life in community‐dwelling older adults as well as in individuals with cancer …”
mentioning
confidence: 99%